Mitigating the ripple effects of urbanization on farmland productivity and ecological security through inclusive urbanization strategies - Guohua Hu; Xia Li; Xiaoping Liu; Shaojian Wang; Xiaoling Zhang; Xun Shi; Xuemei Bai; Klaus Hubacek (npj Urban Sustainability)
Abstract Rapid urbanization in China poses significant threat to food security by diminishing high-quality farmland. This study examines the unintended consequences of urban expansion, referred to as “ripple effects”, where urban land displaces high-quality farmland, subsequently replaced by less productive natural land, resulting in reducing productivity to 62.5% of its original potential. While most research focuses on the direct impacts of urbanization on farmland, our study highlights the often-neglected indirect effects. We propose that urbanization can paradoxically improve farmland security by curbing excessive rural land development, a factor frequently neglected in prior studies. Our findings suggest that inclusive urbanization strategies could potentially free up to 5.77 million hectares of farmland, increasing food production by approximately 60.23 million tons. This research provides a novel perspective on the urbanization-farmland conundrum by integrating rural land use changes and advocating for a migrant-inclusive approach that balances sustainable urban growth with farmland preservation.